Level of knowledge regarding management of patients with permanent pacemaker among nurses - Ismail, Muhamad Al Muizz; Ibrahim, Nor Marini; Che Hasan, Muhammad Kamil (2019)
Objective: Pacemaker may induce musculoskeletal attention of the diaphragm, the pectoral or the intercostal muscles due to extracardiac stimulation normally. The increase in the number of patients with the need for pacemaker implant assistance in the health services sector in Malaysia has resulted in an increased need for nurses to have expertise in patient care with pacemaker implantation. Therefore, this study was conducted to analyze the level of knowledge among nurses regarding the management of patients with pacemaker implantation.